PENINGKATAN LITERASI SAINS DAN KETERAMPILAN PROSES SAINS TERINTEGRASI MAHASISWA CALON GURU SD - MUKTAR B PANJAITAN; ANDRIONO MANALU (LP2MTBM MAKARIOZ, 2019)
The purpose of this study is to describe and analyze the improvement of science literacy and integrated science process skills of students in Low Class Science courses in elementary school teacher candidates. Sample determination using Simple Random Sampling technique. Data collection was done using observation, questionnaires and written tests of scientific literacy & integrated science process skills. Data analysis using descriptive statistics and inferential statistics in paired t test. The inquiry learning modification model is effective in improving science literacy & integrated science process skills of Students with 0.3 <n gain <0.7. Inferential statistics also show a sig value: p < 0.05 that there are significant differences after learning using a modified inquiry model.